Chronic Disease Self-Management Education (CDSME) Program Delivery and Attendance among Urban-Dwelling African Americans - Chivon A Mingo; Matthew Lee eSmith; SangNam eAhn; SangNam eAhn; Luohua eJiang; Jinmyoung eCho; Samuel D Towne; Marcia Gail Ory (Frontiers Media S.A., 2015)
.